Análise do processo de degradação/desertificação na bacia do Rio Taperoá-PB através de indicadores e geotecnologias - Lima, Priscila Pereira Souza de (2014)
Given the complexity of the phenomenon of degradation/desertification in semi-arid northeast it becomes increasingly necessary intensification of studies in which the process, showing its size and the impacts of human activities on the landscape areas in the region. Therefore, several studies have used methods that make use of geotechnology and indicators for analysis of this phenomenon, considering mitigation actions and understanding of the same .Thus, the present study was to scope the spatio- temporal analysis of the degradation / desertification in Taperoá River Basin, through the integration of the physical environmental and socioeconomic indicators, with the support of geotechnology. As a methodological approach to analyze the evolution of the socioeconomic indicators were used the data of the last three demographic and agricultural census , checking the status of improvement or worsening of each indicator in full or partially municipalities in the basin. For physical environmental indicators techniques of digital image processing and GIS were used. Finally maps the evolution of each group of indicators are generated and made the spatial correlation between the levels of desertification. As a result of the levels of desertification was identified that 49.15% of the total area in basin are on average level; 36.81 % at low level and 11.08% at a high level; pointing to a recovery process of vegetation in the region over the past twenty years. The spatial correlation with the social and economic indicators was considered indirect, due to the influence of external factors such as public politics. Have the spatial correlation with agriculture indicators presented more directly, since they reflect the intensity of land use. There is a strong spatial correlation between the levels of rainfall, the topography of the region and the state of vegetation cover and therefore, the levels of desertification.